Філософія права як наука і навчальна дисципліна - Костицький, М.В. (Інститут держави і права ім. В.М. Корецького НАН України, 2003)
Философия права есть самостоятельная наука, одновременно соответствующая и всем параметрам научной дисциплины. В Украине философия права переживает интенсивное развитие, что с необходимостью предполагает глубокое исследование таких ее составляющих, как правовая онтология, правовая гносеология, правовая аксиология, философско-правовая антропология и, конечно же, методология правоведения. Philosophy of law is an independent science, concurrently meeting all requirements expected of an academic
subject. The philosophy of law in Ukraine is characterized by the intensive development, which presupposes
profound research in such its areas as legal onthology, legal gnoseology, legal axiology, philosophical
anthropology of law and, certainly, methodology of legal studies.